Sciencemetrics studies in agricultural sciences: measurement of the performance of the scientific production of the Institute of Animal Science in the period 1996-2013 from Scopus - Mesa, Dianelis (Cuban Journal of Agricultural Science, 2017)
A study was realized for stating the evolution that science has had in the Institute of Animal Science through the use of bibliometrics indicators. In this case production indicators, of scientific collaboration and of citation for describing the performance of the publications of this institution in the period 1996-2013 are considered in the Database Scopus. A theoretical trip through the main metric disciplines is realized for knowing its study objective and emphasis is made on the sciencemetrics, the existing situation in our region and specifically in Cuba on this matter. The importance of the adequate use of the indicators as tools capable of expressing the reality present in each context is undertaken. It is suggested systematizing the use of the sciencemetrics indicators in the redesigning of scientific policies.